2010
DOI: 10.1214/09-aop505
|View full text |Cite
|
Sign up to set email alerts
|

Local limit theorems in free probability theory

Abstract: In this paper, we study the superconvergence phenomenon in the free central limit theorem for identically distributed, unbounded summands. We prove not only the uniform convergence of the densities to the semicircular density but also their $L^p$-convergence to the same limit for $p>1/2$. Moreover, an entropic central limit theorem is obtained as a consequence of the above results.Comment: Published in at http://dx.doi.org/10.1214/09-AOP505 the Annals of Probability (http://www.imstat.org/aop/) by the Instit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…The results in [9] were extended to measures with unbounded support in [23], and a local almost everywhere convergence to freely stable densities was proved later in [18]. Our proofs in this paper rely on analytic subordination of free convolution and a technique of recasting weak convergence of measures into local uniform convergence of these subordination functions, where the latter has to do with the asymptotics of certain integral transforms (see Section 3).…”
Section: Introductionmentioning
confidence: 94%
“…The results in [9] were extended to measures with unbounded support in [23], and a local almost everywhere convergence to freely stable densities was proved later in [18]. Our proofs in this paper rely on analytic subordination of free convolution and a technique of recasting weak convergence of measures into local uniform convergence of these subordination functions, where the latter has to do with the asymptotics of certain integral transforms (see Section 3).…”
Section: Introductionmentioning
confidence: 94%
“…In particular, the preceding result generalizes the superconvergence for measures with finite variance in [16] to the entire free domain of attraction of the semicircular law.…”
Section: Stable Approximationmentioning
confidence: 54%
“…This phenomenon was called superconvergence in that paper. The assumption that X i be bounded was removed in subsequent work of the second author [16]. Even when the variables X i are not identically distributed, but are uniformly bounded, the support of S n was shown by Kargin [12] to converge to the interval [−2, 2] as n → ∞.…”
Section: Introductionmentioning
confidence: 99%
“…Note that in the analytic theorems, the hypothesis on the distributions are identical to those in the usual CLT. On the other hand, in [9] and [26] the authors showed that the mode of convergence in the free CLT is actually much stronger than the classical convergence in distribution. In all these results, the limiting distribution is the semicircle law.…”
Section: Introductionmentioning
confidence: 99%